Marine Oomycetes of the Genus Halophytophthora Harbor Viruses Related to Bunyaviruses - Botella, Leticia; Janoušek, Josef; Maia, Cristiana; Jung, Marilia Horta; Raco, Milica; Jung, Thomas (Frontiers in Microbiology, 2020)
We investigated the incidence of RNA viruses in a collection of Halophytophthora spp. from estuarine ecosystems in southern Portugal. The first approach to detect the presence of viruses was based on the occurrence of dsRNA, typically considered as a viral molecule in plants and fungi. From 73 Halophytophthora isolates, two dsRNA-banding patterns were observed (~7 and 9 kb) in few isolates (9.6 %), and, consequently, two dsRNA-hosting isolates were chosen for performing stranded mRNA sequencing for the de novo assembling of viruses. A total of eight putative novel virus species with genomic affinities to members of the Order Bunyavirales were detected and their full-length genome characterised by RACE. Based on the direct partial amplification of their RdRp by RT-PCR multiple viral infections occur in both isolates selected. Likewise, the screening of those viruses in the whole collection of Halophytophthora isolates showed that their occurrence is limited to one single Halophytophthora species. To our best knowledge, this is the first report confirming the presence of negative (-) ssRNA viruses in marine oomycetes.